Organizational culture, compensation and employee engagement influence on organizational citizenship behavior - Dewi Susita, Ardiansyah, Hamidah, (Opción, 2020)
The study aims to examine the influence of organizational culture, compensation, and employee attachment to organizational citizenship behavior and its implications for the turnover intention on employees internal of the Matahari dept. store via testing, data collection and model development is a structural equation model. Data were analyzed using LISREL 8.8 statistical software tools. As a result, organizational culture has a positive direct effect on organizational citizenship behavior. In conclusion, employee engagement has a significant negative influence on turnover intention mediated by organizational citizenship behavior